PENGARUH PRICE EARNING RATIO (PER), EARNING PER SHARE (EPS), DEVIDEND YIELD RATIO (DYR), DIVIDEND PAYOUT RATIO (DPR), BOOK VALUE PER SHARE (BVS) DAN PRICE BOOK VALUE(PBV ) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - Lidia Desiana (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
One of the financial ratios that can be used to provide information on how much society (investors) or shareholders appreciates the company, so they want to buy stockof the company at a higher price than the book value of stock is the ratio of share capital or market ratio. This research aims to prove the influence of PriceEarning Ratio (PER), Earning Per Share (EPS), Devidend Yield Ratio (DYR), Dividend Payout Ratio (DPR), Book Value per Share (BVS) and Price Book Value (PBV) Sharia shares. The sample in this research consists of two sub-sector food and beverage companies listed in Jakarta Islamic Index, namely PT. Indofood CBP Sukses Makmur, Tbk and PT. Indofood Sukses Makmur, Tbk. To explain the influence of these variables, the data obtained in this research were analyzed using multiple linear regression model. The result of T test shows that Price Earning Ratio (PER), EarningPer Share (EPS), Book Value Per Share (BVS) and Price Book Value (PBV) have an effect on stock price. Devidend Yield Ratio (DYR) and Devidend Payout Ratio (Parliament) partially have no effect on stock prices. F test results show that Price Earning Ratio (PER), Earning Per Share (EPS), Devidend Yield Ratio (DYR), Devidend Payout Ratio (DPR), Book Value Per Share (BVS), Price Book Value (PBV) simultanly have effect on stock prices. Keywords: Price Earning Ratio, Earning Per Share (EPS), Devidend Yield Ratio (DYR), Devidend Payout Ratio (DPR), Book Value Per Share (BVS), Price Book Value (PBV) and Sharia Stock Price